Manipulation of Cannabinoid Biosynthesis via Transient RNAi Expression - Matchett-Oates, Lennon; Spangenberg, German C.; Cogan, Noel O. I. (Frontiers in Plant Science, 2021)
Cannabis sativa L. produces unique phytocannabinoids, which are used for their pharmaceutical benefits. To date, there are no reports of in vivo engineering targeting the cannabinoid biosynthesis genes to greater elucidate the role each of these genes play in synthesis of these medically important compounds. Reported here is the first modulation of cannabinoid biosynthesis genes using RNAi via agroinfiltration. Vacuum infiltrated leaf discs of the Cannbio-2 C. sativa strain, transfected with different RNAi constructs corresponding to THCAS, CBDAS and CBCAS gene sequences, showed significant downregulation of all cannabinoid biosynthesis genes using Real-Time Quantitative PCR. Using RNAi, significant off-targeting occurs resulting in the downregulation of highly homologous transcripts. Significant (p <0.05) down regulation was observed for THCAS (92%), CBDAS (97%) and CBCAS (70%) using pRNAi-GG-CBDAS-UNIVERSAL. Significant (p <0.05) upregulation of CBCAS (76%) and non-significant upregulation of THCAS (13%) was observed when transfected with pRNAi-GG-CBCAS, suggesting the related gene’s ability to synthesize multiple cannabinoids. Using this approach, increased understanding of the relationship between cannabinoid biosynthesis genes can be further elucidated. This RNAi approach enables functional genomics screens for further reverse genetic studies as well as the development of designer cannabis strains with over-expression and/or downregulation of targeted cannabinoid biosynthesis genes. Functional genomics screens such as these will further provide insights into gene regulation of cannabinoid biosynthesis in Cannabis.